Concerning the Effect of a Viscoelastic Foundation on the Dynamic Stability of a Pipeline System Conveying an Incompressible Fluid - Vincent Olunloyo; Charles Osheku; Patrick Olayiwola (Journal of applied and computational mechanics, 2016)
In this paper, we present an analytical method for solving a well-posed boundary value problem of mathematical physics governing the vibration characteristics of an internal flow propelled fluid-structure interaction where the pipeline segment is idealized as an elastic hollow beam conveying an incompressible fluid on a viscoelastic foundation. The effect of Coriolis and damping forces on the overall dynamic response of the system is investigated. In actuality, for a pipe segment supported at both ends and subject to a free motion, these two forces generate conjugate complex frequencies for all flow velocities. On employing integral transforms and complex variable functions, a closed form analytical expression is derived for the overall dynamic response. It is demonstrated that a concise mathematical expression for the natural frequency associated with any mode of vibration can be deduced from the algebraic product of the complex frequency pairs. By a way of comparative analysis for damping decrement physics reminiscent with laminated structures, mathematical expressions are derived to illustrate viscoelastic damping effects on dynamic stability for any flow velocity. The integrity of the analytical solution is verified and validated by confirming theresults in literature in appropriate asymptotic limits.